Maculopathy Due to the R345W Substitution in Fibulin-3: Distinct Clinical Features, Disease Variability, and Extent of Retinal Dysfunction - Michaelides, Michel; Jenkins, Sharon A; Brantley, Milam A., Jr; Andrews, Richard M; Waseem, Naushin; Luong, Vy; Gregory-Evans, Kevin; Bhattacharya, Shomi S; Fitzke, Fred W; Webster, Andrew R (Investigative ophthalmology & visual science, 2006)
To determine (1) clinical features that distinguish maculopathy due to the R345W substitution in fibulin-3 from other forms of inherited or early-onset drusen, (2) the phenotypic variability, and (3) the extent of retinal disease in those with a positive molecular diagnosis. Affected individuals underwent ophthalmic examination, digital color fundus photography, fundus autofluorescence (AF) imaging, and psychophysical testing with automated photopic and dark-adapted perimetry and fine matrix mapping. Blood samples were taken for DNA extraction and screening for the R345W mutation in fibulin-3. Patients were subsequently divided into mutation-positive and -negative groups, to compare the identified phenotypic findings in these two sets of subjects. Twenty-nine subjects from 19 families were ascertained with inherited or early-onset drusen. Twenty-four (83%) subjects from 15 families were found to harbor the R345W fibulin-3 mutation. Peripapillary deposition and a radial distribution of macular drusen were consistent, distinguishing signs in the mutation-positive group. Subretinal neovascular membrane (SRNVM) was a rare occurrence, affecting only 1 of 48 eyes, whereas hyperpigmentation and atrophy of the retinal pigment epithelium (RPE) were common in older mutation-positive patients. Increased AF corresponding to the drusen was detected in both the mutation-positive and -negative groups. The phenotype in the group of patients positive for the R345W mutation was extremely variable, with evidence of interocular, intrafamilial, and interfamilial variability in visual loss, natural history, ophthalmoscopic findings, autofluorescence imaging, and psychophysical data. The novel finding of nonpenetrance was observed in a 62-year-old asymptomatic, mutation-positive man. The findings from detailed perimetry performed on a subset of subjects were consistent with the presence of widespread retinal dysfunction not isolated to the macula. Marked inter- and intrafamilial variation associated with the fibulin-3 R345W mutation in terms of retinal appearance, severity, progression, and nonpenetrance were identified. It was noted that SRNVM is a rare occurrence in R345W fibulin-3 maculopathy. These findings are helpful for advice regarding prognosis and for genetic counseling. The findings established that the presence of peripapillary deposit is highly likely to indicate that a patient carries the R345W mutation.